Asian financial crisis financial, structural and international dimensions - Choi, J. Jay (JAI, 2000)
This edited volume is a collection of original theoretical, empirical, institutional or policy-oriented articles on all dimensions of the Asian financial crisis. A unique feature of this book is its multi-faceted, yet in-depth articles on various dimensions of the Asian financial crisis written by policy-makers and practitioners as well as scholars around the world. It includes financial, structural, cultural, and international dimensions of the Asian financial crisis regarding its causes, consequences, policies, and lessons. As such, it offers an excellent one-stop collection of in-depth research articles on the topic. The book includes nineteen articles on the overview of the crisis, international capital flows and crisis, reform in financial and industrial sectors, and cultural and post-crisis opportunities.
Keywords: Financial crises -- Asia.; Business cycles -- Asia.; elektronické knihy; electronic books